Quantitative and Qualitative Microbiological Profiles of the Apollo 10 and 11 Spacecraft - Puleo, John R. (1970)
Microbiological profiles were determined for surfaces of the command module, lunar module (ascent and descent stages), instrument unit, Saturn S-4B stage, and the spacecraft lunar module adapter of the Apollo 10 and 11 spacecraft. Average levels of contamination of the command module were 2.1 × 10(4) and 2.7 × 10(4) microorganisms per ft(2) for Apollo 10 and 11, respectively. With the exception of the exterior surfaces of the ascent stage of the lunar module and the interior surfaces of the command module, average levels of microbial contamination on all components of the Apollo 11 were found to be lower than those observed on Apollo 10. For each Apollo mission, approximately 2,000 colonies were picked from a variety of media and identified. The results showed that approximately 95% of all isolates were those considered indigenous to humans; the remaining were associated with soil and dust in the environment. However, the ratio of these two general groups varied depending on the degrees of personnel density and environmental control associated with each module.